2018
DOI: 10.1002/ptr.6038
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic and antidepressant activities of Pelargonium roseum essential oil on Swiss albino mice: Possible involvement of serotonergic transmission

Abstract: The anxiolytic and antidepressant activities of the Reunion Geranium (Pelargonium roseum Willd) essential oil (EO) were evaluated in male Swiss albino mice by intraperitoneal administration of 10, 20, and 50 mg/kg bw using elevated plus maze (EPM), open-field test (OFT), and forced swimming test (FST). Moreover, we evaluated whether the 5-HT and GABA -benzodiazepine receptor systems are involved in the anxiolytic effects through the coadministration of WAY-100635 (a selective 5-HT receptor antagonist) and flum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Moreover, WAY100635, a 5-HT receptor antagonist, blocks the action of the essential oil of lavender while the use of antagonists of GABA-A receptor is devoid of effect [42, 43]. Similar data are also achieved by Galdino et al and by Tabari et al who have observed anxiolytic effects after systemic injection of Spiranthera odoratissima and Rose geranium essential oils counteracted by pretreatment with 5-HT1A receptor antagonists but not by FLZ [44, 45].…”
Section: Discussionmentioning
confidence: 68%
“…Moreover, WAY100635, a 5-HT receptor antagonist, blocks the action of the essential oil of lavender while the use of antagonists of GABA-A receptor is devoid of effect [42, 43]. Similar data are also achieved by Galdino et al and by Tabari et al who have observed anxiolytic effects after systemic injection of Spiranthera odoratissima and Rose geranium essential oils counteracted by pretreatment with 5-HT1A receptor antagonists but not by FLZ [44, 45].…”
Section: Discussionmentioning
confidence: 68%
“…Complementary and alternative therapies may play an important role in the clinical treatment of anxiety disorders (Hazim et al, 2014; Thorn et al, 2016). Compared to classical anxiolytic drugs, use of complementary and alternative medicine could show fewer side-effects (Li et al, 2016; Abouhosseini Tabari et al, 2018). The Gan-Mai-Da-Zao (GMDZ) decoction is one of the most famous herbal prescriptions in Chinese medical book Jin Gui Yao Lue (Medical Treasures of the Golden Chamber), which is written by medical sage Zhang Zhongjing (Ruan, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This result is confirmed by a study of Pelargonium roseum essential oil, which contains monoterpenes, and is similar to the essential oil of Lippia sidoides Cham. The locomotor activity of the animals did not change, which also demonstrates its antidepressant effect [47].…”
Section: Discussionmentioning
confidence: 76%